Functional hybrid molecules for the visualization of cancer: PESIN-homodimers combined with multimodal molecular imaging probes for positron emission tomography and optical imaging : suited for tracking of GRPR-positive malignant tissue - Hübner, Ralph; Cheng, Xia; Wängler, Björn; Wängler, Carmen (Chemistry - a European journal, 2020)
We describe multimodal imaging probes for gastrin-releasing peptide receptor (GRPR)-specific targeting suited for positron emission tomography and optical imaging (PET/OI), consisting of PESIN (PEG3-BBN7-14) dimers connected to multimodal imaging subunits. These multimodal agents comprise a fluorescent dye for OI and the chelator ((1,4,7-triazacyclononane-4,7-diyl)diacetic acid-1-glutaric acid) (NODA-GA) for PET radiometal isotope labelling. Special focus was put on the influence of the used dyes on the properties of the whole bioconjugates. For this, several compounds with different fluorescent dyes and non-dye carrying subunits were synthesized and investigated. As fluorescent dyes, dansyl, NBD, derivatives of fluorescein, coumarin and rhodamine as well as three pyrilium-based dyes were employed. Considerable influence of the charge of the colored unit on hydrophilicity as well as in vitro target receptor binding was observed and classified. High radiochemical yields and purities were found during radiolabeling of the multimodal imaging subunits as well as their GRPR-specific bioconjugates with 68Ga. Examinations of the photophysical properties of both molecule species displayed no loss or alteration of fluorescence characteristics.
Version of record online: October 28, 2020
Gesehen am 20.01.2022